2019
DOI: 10.3390/jcs3020039
|View full text |Cite
|
Sign up to set email alerts
|

pH-Triggered Interfacial Interaction of Kaolinite/Chitosan Nanocomposites with Anionic Azo Dye

Abstract: Advanced engineering of naturally occurring materials opens new doors in nanoscience and nanotechnology for the separation and/or removal of environmental hazards. Here, a series of nanocomposites containing kaolinite and chitosan varying in the range of 20 to 80% (w/w) kaolinite were used for the adsorptive removal of a reactive textile dye, Remazol Red, from an aqueous solution. Batch experiments were carried out to investigate the effects of pH, contact time, and initial dye concentration on the adsorption … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…Regeneration studies were also carried out, and results showed that 99% of adsorbents could be regenerated. The results proved that chitosan-kaolinite nanocomposites could be used as potential adsorbents to remove azo dyes [42].…”
Section: Wastewater and Industrial Effluent Treatmentmentioning
confidence: 78%
“…Regeneration studies were also carried out, and results showed that 99% of adsorbents could be regenerated. The results proved that chitosan-kaolinite nanocomposites could be used as potential adsorbents to remove azo dyes [42].…”
Section: Wastewater and Industrial Effluent Treatmentmentioning
confidence: 78%
“…At 290 • C, the rate of maximum decomposition (R max ) was 17 µg/ • C for K 0 SNC film. A slightly higher decomposition rate, 22 µg/ • C, was found for the K 5 SNC and K 10 SNC films at 300 • C and 312 • C. Besides, the K 15 SNC film showeda drastically increased decomposition rate of 30 µg/ • C at 314 • C, which is lower than that obtained from K 20 SNC, R max = 36 µg/ • C, at T peak = 316 • C, indicating that the K 20 SNC film is more thermally unstable that the K 15 SNC film [27][28][29][30][31][32][33][34][35][36]. Figure 5 shows TMA and differential thermal mechanical analysis (DTMA) graphs obtained from 0% to 20% kaolin containing starch films.…”
Section: Thermogravimeric Analysis (Tga)mentioning
confidence: 78%
“…It was found that the degrading utilization of PNP dramatically reduced at pH 4.0 and 8.0, while it increased highly when the pH value was 6.0. This finding has been reflected by the fact that the positively charged surface of the MOF 1 can benefit the electrostatic interactions with the anionic dyes (Figure S10e) [57,58].…”
Section: Diffuse Reflectance Spectroscopy and Photocatalytic Propertiesmentioning
confidence: 95%